The Distinction Among Political Humor Meme Creators in the Political Field of The 2019 Presidential Campaign for The Jokowi-Amin Pairing on Twitter - Ajeng Iva Dwi Febriana; Umaimah Wahid; Alexander Seran (Future Science, 2023)
Political meme creators play an important role in conveying political messages, shaping public opinion as well as the practice of decision making through the political memes produced. Political memes circulating on various social media during the campaign period of the 2019 Presidential Election 2019 largely contain hate speech, hoax and character assassination. Nearing the grand campaign for the 2019 presidential election, political memes were popping up everywhere, containing humorous narratives in conveying political messages and support to the 2019 Jokowi-Amin pairing, which were distinct when compared to political memes in general. This study aimed to explore distinct actions by political humor meme creators around the grand campaign for the 2019 presidential election for the 2019 Jokowi-Amin pairing on Twitter. This study used a qualitative approach with the case study method. Primary data were obtained from observations and in-depth interviews with political humor meme creators who produced political humor memes nearing the grand campaign for Jokowi-Amin. Secondary data were sourced from digital materials (political memes, political humor memes, videos, and digital media). The results showed that the distinct behaviors displayed by these political humor meme creators influenced by habitus and capital aspects which aim to describe tastes and form classes in their social structure. Tastes are not only limited to consumption patterns of food, clothing and culture, but also include political ways of political humor meme creators who use humorous narratives in political memes to show their social class by not resorting to hate speech in winning the Jokowi-Amin pairing.